Quality of Service in the Digital Era: Challenges and Opportunities - Rauf, Nuzmerini; Djou, Sitti Husna Noviana; Ma’ruf, Fatmah; Anani, Siske; Rizal, Rizal (Westscience Press, 2024)
This article discusses the quality of service in the context of the digital era, identifying the challenges and opportunities faced by the organization. With the advancement of technology, the interaction between service providers and customers is becoming easier, but it also brings new challenges such as data security and ever-increasing expectations. This study examines various strategies that can be applied to improve service quality, including the use of artificial intelligence and data analytics to understand customer needs. Additionally, this article emphasizes the importance of employee training in dealing with these changes, as well as innovative approaches to creating a better customer experience. The results show that despite the challenges, the digital era also offers significant opportunities for companies to improve service and build stronger relationships with customers.